Penyalahgunaan Teknologi Informasi Sebagai Sebab dari Tindak Kekerasan yang Dilakukan oleh Remaja (Tinjauan kasus pada salah satu narapidana di Lembaga Pemasyarakatan Khusus Anak Kelas 1 Tangerang) - H, Herlambang (Media Hukum Indonesia (MHI), 2024)
Violence or abuse often occurs either at home or on the streets, this can have detrimental consequences for others because a sense of security is no longer obtained. The rampant violence triggered by brawls by teenagers cannot be separated from the influence of the environment, youth and information technology. Information technology has an influence in changing the order of community life. Brawls in this era still occur a lot involving teenagers, students caused by problems involving groups, such as between motorcycle gangs, between villages and brawls between schools. Brawls involving teenagers are caused by wanting to find their identity, even wanting to be seen as popular from others or their groups. The trigger for violence or brawls is the existence of social media that is not limited, can be accessed by anyone, and even becomes a medium for brainwashing teenagers in the name of solidarity. In this article, the author informs about perpetrators of violence among teenagers who injured their victims with sharp weapons. This was done because of an invitation from the Administrator of social media in the name of solidarity. From the results of the interview, information was obtained that the suspect was charged with Article 90 of the Criminal Code concerning abuse. The sentence imposed on him was a 9-year prison sentence, a verdict of 4 years and 9 months.